ANTICIPATING RADICAL UNDERSTANDING IN CHILDREN: STRATEGIES OF PARENTS IN DEVELOPING PLURALISM CHARACTER - Putri, Devi Sutrisno; Siswanto, Edi; Nurhayati, Nurhayati (Ganesha Civic Education Journal, 2023)
Actions of radicalism are now starting to become epidemic in all circles. It can be seen several years ago, there were suicide bombings in the Surabaya. church involving children, and other actions that led to the imposition of the ideology of cultural truth, even religion on other parties outside of a particular culture or religion. The issue of radicalism should be recognized and efforts must be made to prevent the spread of the claim of truth. The phenomenon of conflict that comes and goes due to differences makes thinking backward to relate these incidents to the educational process that has been implemented from parents to children. Parenting skills are abilities possessed by parents in raising and educating children which greatly affect the development of children's characteristics in the future. The introduction of existing diversity should start from where the child is. The character of pluralism is deemed important to be developed in the context of preventing radical movements in Indonesia because the management of differences is so primordial from any truth of community groups, it is necessary to take preventive action, for example in the realm of education, especially non formal education from parents. This research was a descriptive qualitative research with the type of case study research in Srisawahan Village, Central Lampung. The informants in this study were people in Srisawahan Village, Central Lampung. This study aims to find a strategy for developing pluralistic character and tolerance in children to prevent radicalism and movements from an early age.